2015
DOI: 10.1158/1535-7163.mct-14-0208
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Dose Escalation Overcomes Transient Resistance in Clear Cell Renal Cell Carcinoma and Is Associated with Epigenetic Modifications

Abstract: Sunitinib is considered a first-line therapeutic option for patients with advanced clear cell renal cell carcinoma (ccRCC). Despite sunitinib clinical efficacy, eventually patients develop drug resistance and disease progression. Herein, we tested the hypothesis whether initial sunitinib resistance may be transient and could be overcome by dose increase. In selected patients initially treated with 50 mg sunitinib and presenting with minimal toxicities, sunitinib dose was escalated to 62.5 mg and/or 75 mg at th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 32 publications
7
67
0
1
Order By: Relevance
“…This dual mechanism thus not only can contribute to resistance to sunitinib, but also can represent a mechanism by which higher doses of sunitinib exert cytotoxicity. Several reports have shown that cancer patients who resisted and subsequently progressed in response to clinically approved doses of sunitinib as well as during "sunitinib-off " period can be sensitized to sunitinib by escalating its dose (11,48). Our data shown here provide a potential molecular explanation for this reported observation, as higher doses of sunitinib could shift the response of tumor cells toward MCL-1 destabilization and mTOR inhibition, with an increased anticancer effect.…”
Section: Sunitinib Exerts Dual Effects On Mcl-1 and Mtor In Tolerant Andsupporting
confidence: 56%
See 1 more Smart Citation
“…This dual mechanism thus not only can contribute to resistance to sunitinib, but also can represent a mechanism by which higher doses of sunitinib exert cytotoxicity. Several reports have shown that cancer patients who resisted and subsequently progressed in response to clinically approved doses of sunitinib as well as during "sunitinib-off " period can be sensitized to sunitinib by escalating its dose (11,48). Our data shown here provide a potential molecular explanation for this reported observation, as higher doses of sunitinib could shift the response of tumor cells toward MCL-1 destabilization and mTOR inhibition, with an increased anticancer effect.…”
Section: Sunitinib Exerts Dual Effects On Mcl-1 and Mtor In Tolerant Andsupporting
confidence: 56%
“…Sunitinib is approved for treating patients with advanced renal cell carcinoma (2), pancreatic neuroendocrine tumors (3), and gastrointestinal stromal tumors (4,5) and is being tested in other types of cancer including osteosarcoma (6), colorectal cancer (7), and melanoma (8). However, a substantial percentage of patients are intrinsically resistant to sunitinib, and most patients who show initial response to treatment with sunitinib eventually relapse and develop progressive disease secondary to acquired sunitinib resistance, resulting in a modest overall therapeutic benefit (9)(10)(11)(12)(13). Optimal clinical use of sunitinib therefore relies on better understanding of the mechanisms of tumor resistance to this anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…This observation may at least in part explain better DFS benefit of sunitinib in S-TRAC, relative to that reported in the ASSURE trial. In consequence, dose escalations such as described by Bjarnason et al [11,12], might result in better DFS and possibly also in better OS and dose individualization may warrant consideration, if adjuvant sunitinib therapy is considered.…”
Section: Cuaj -Consensus Statementmentioning
confidence: 99%
“…6 This may explain the clinical observation of reduced toxicity as patients stay on tyrosine kinase inhibitor (TKI) therapy. These observations led to our early attempts to individualize dose and schedule to toxicity, 7,8 assuming toxicity might correlate better with sunitinib pharmacodynamics (PD) 9 and would take into account the inter-individual differences in sunitinib PK, potential decline in PK over time, individual singlenucleotide polymorphisms, and interactions with other drugs and that can impact the PK for sunitinib.…”
Section: Maximizing Drug Exposure Is Importantmentioning
confidence: 99%